Direitos de Propriedade, Custos de Transação e Concorrência: o Modelo de Barzel DOI: http://dx.doi.org/10.18836/2178-0587/ealr.v2n1p95-114 - Fowler de Avila Monteiro, Guilherme (2011)
Barzel (1994, 1997, 2003) proposed an economic approach of property rights. The current article examines this approach, providing an overview of his theory. Particularly, the paper identifies and discusses three basic concepts: asset as a bundle of attributes, economic property rights, and public domain. In addition, the article examines two related aspects: the concept of transaction costs and the relationship between competition and value appropriation. More than a description, the article represents an attempt to organize the thinking about the economic analysis of property rights.